2021
DOI: 10.1038/s41598-021-94500-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of the murine ischemic retina and its response to Aflibercept (VEGF-Trap)

Abstract: Ischemic retinal dystrophies are leading causes of acquired vision loss. Although the dysregulated expression of the hypoxia-responsive VEGF-A is a major driver of ischemic retinopathies, implication of additional VEGF-family members in their pathogenesis has led to the development of multivalent anti-angiogenic tools. Designed as a decoy receptor for all ligands of VEGFR1 and VEGFR2, Aflibercept is a potent anti-angiogenic agent. Notwithstanding, the molecular mechanisms mediating Aflibercept’s efficacy remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 139 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…However, the expression of Ang-2 in the context of high VEGF levels contributes to angiogenesis, facilitating the responsiveness to VEGF [43]. Additionally, the inhibition of VEGF appeared to downregulate the levels of Ang-2, leading to normal protein levels in the vitreous and messenger RNA (mRNA) in the retina [44,45]. These findings were interpreted in light of clinical trial results from nesvacumab, a fully human IgG1 monoclonal antibody binding Ang-2 plus aflibercept that exhibited no significant benefits compared to aflibercept alone in treating both neovascular AMD and diabetic macular edema [46][47][48].…”
Section: An Overview Of Angiogenic Factors Involved In Angiogenesismentioning
confidence: 99%
“…However, the expression of Ang-2 in the context of high VEGF levels contributes to angiogenesis, facilitating the responsiveness to VEGF [43]. Additionally, the inhibition of VEGF appeared to downregulate the levels of Ang-2, leading to normal protein levels in the vitreous and messenger RNA (mRNA) in the retina [44,45]. These findings were interpreted in light of clinical trial results from nesvacumab, a fully human IgG1 monoclonal antibody binding Ang-2 plus aflibercept that exhibited no significant benefits compared to aflibercept alone in treating both neovascular AMD and diabetic macular edema [46][47][48].…”
Section: An Overview Of Angiogenic Factors Involved In Angiogenesismentioning
confidence: 99%
“…1 Comparable findings are reported using an oxygen-induced retinopathy model in mice. 2 Rojo Arias et al 2 reported an increase of ANG2 expression in response to hypoxia, as well as a consistent down-regulation of ANG2 expression after treatment with aflibercept.…”
mentioning
confidence: 96%